Implementasi Metode Profile Matching untuk Penentuan Mahasiswa Berprestasi - Siagian, Edward Robinson (MEANS (Media Informasi Analisa dan Sistem), 2020)
Decision support systems developed at the beginning of the era of distributed computing and began to develop in the 1960-1970s, as a result of a number of other factors: hadware and software technology, research efforts by academics from universities, began to grow awareness of the support of a decision and the desire to obtain better information. In this study, a case will be raised, which is looking for the best alternative based on student competence in the "XYZ" educational institution by applying the profile matching method. This method was chosen because it is able to select the best alternative from the aspects of existing criteria. The study was conducted to find the value of weight for each aspect, such as examples of academic aspects and non-academic aspects of students, then the ranking process of selected prospective students who have been selected, and the output of the application can help decision makers in choosing alternative students who excel.